Perlindungan Hukum Bagi Pemegang Hak Atas Tanah Dengan Sertifikat Hgb Yang Sudah Habis Masa Berlakunya (STUDI KASUS NOMOR 499/PDT.G/2011/PN.JKT.PST) - Nurokhim HasbiIsmail (Jurnal Penelitian Hukum Legalitas, 2016)
This type of research is a normative research that is analytical descriptive. The data collection technique used is literature study. Legal materials used include (1) the 1945 Constitution, Law No. 5 of 1960, Law No. 40 of 1996, Government Regulation No. 24 of 1997 and; (2) Secondary law materials: Scientific books; Documents; Reports and materials from the internet.Obstacles that have been experienced by the justice seekers in court resulted in relatively simple alternative (non lettigation) dispute resolution, shorter time and lower cost. This model is called Alternative Dispute Resulution (ADR)